Unilateral acromial dimple in an infant: A case report and review of the literature - Deepa Vasireddy,; Srikrishna Varun Malayala,; Paavani Atluri, (Indian Journal of Case Reports, 2021)
Skin depressions overlying the area of the acromion process of the scapula are known as acromial dimples. They are rare in occurrence and usually tend to be bilateral. A unilateral acromial dimple is even rarer and has not been published in the literature so far. Here, we present the case of a unilateral acromial dimple in a 1-month-old male infant who presented to the clinic with a persistent skin lesion on his posterior left shoulder since birth. On examination, he had a solitary dimple overlying the left acromion process. He had a full range of motion of the left upper extremity without weakness or discomfort. Acromial dimples have been described to occur with 18q deletion syndrome, Apert syndrome, and Say syndrome. Acromial dimple when found in isolation without affecting the upper extremity movement does not require further management.